How to support cleantech start-ups? Lessons from European venture-capital deals - Monika Köppl-Turyna; Stefan Köppl; Dimitris Christopulos (EcoAustria - Institute for Economic Research, 2023)
In this paper we analyze how different types of venture capital investments - private, public and indirect public - affect performance of "cleantech" start-ups in Europe. We hand collected a unique dataset on the institutional setting (public/indirect/private) of almost 15000 investors in Europe, which we combine with portfolio-company and deals data from Preqin to assess performance. Two results stand out: First, public venture capital does not underperform private venture capital in a broad crosscountry sample of European deals. This is a novel finding, as it doesn't confirm some previous findings in the literature that government-backed VCs underperform their private counterparts. We also find that there is no significant difference between direct and indirect government support of venture capital for cleantech investments. Second, GVCs perform well when they specialize in cleantech investments and are well connected within a network of other investors.
Keywords: G24; G28; H81; L26; D73; 330; venture capital; governmental venture capital; European Investment Fund; public policy; green technology; cleantech